2019
DOI: 10.1007/s00018-019-03057-w
|View full text |Cite
|
Sign up to set email alerts
|

Rab6 regulates cell migration and invasion by recruiting Cdc42 and modulating its activity

Abstract: Rab proteins are master regulators of intracellular membrane trafficking but they also contribute to cell division, signaling, polarization and migration. The majority of the works describing the mechanisms used by Rab proteins to regulate cell motility involve intracellular transport of key molecules important for migration. Interestingly, a few studies indicate that Rabs can modulate the activity of Rho GTPases, important regulators for the cytoskeleton rearrangements, but the mechanisms behind this crosstal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 93 publications
1
19
0
Order By: Relevance
“…Despite this, the elucidation of the specific molecular mechanism by which RAB6 regulates DKK1 autocrine still requires further investigation. Finally, we cannot completely rule out the possibility that RAB6 regulates AEC2 cell proliferation and self-renewal through other potential targets, such as cell division control protein 42 (CDC42) 25 and kinesin-1 46 , all of which were confirmed as targets of RAB6 by other investigators.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Despite this, the elucidation of the specific molecular mechanism by which RAB6 regulates DKK1 autocrine still requires further investigation. Finally, we cannot completely rule out the possibility that RAB6 regulates AEC2 cell proliferation and self-renewal through other potential targets, such as cell division control protein 42 (CDC42) 25 and kinesin-1 46 , all of which were confirmed as targets of RAB6 by other investigators.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, RAB6 regulates the secretion of vesicles and affects the growth and development of zebrafish neurons 23 . Moreover, RAB6 protein is widely involved in various physiological activities such as cell adhesion and migration [24][25][26][27] . We have shown that RAB6 is down-regulated in lung cancer tissues, and its overexpression can inhibit cell proliferation and colony formation in non-small cell lung cancer 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has indicated that cell migratory and invasive processes are strongly correlated with significant cytoskeleton remodelling (Fife et al, 2014). CDC42 is a key regulatory protein for the dynamic structures of the cytoskeleton (Vestre et al, 2019). Several recent studies have highlighted that CDC42 is implicated with trophoblast cell migration (Nicola et al, 2008;Fritz et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This function is often connected to their role in mediating intracellular transport, but can also be associated with their ability to regulate cytoskeleton dynamics (Borg et al, 2014;Kjos et al, 2018;Lanzetti et al, 2004;Linford et al, 2012;Palamidessi et al, 2008). Indeed, Rab proteins can influence cytoskeleton dynamics, for example through crosstalk with Rho GTPases (Borg et al, 2014;Bravo-Cordero et al, 2016;Chevallier et al, 2009;Jian et al, 2016;Margiotta et al, 2017;Palamidessi et al, 2008;Vestre et al, 2019).…”
Section: Introductionmentioning
confidence: 99%